Computational modelling of steel rebars corrosion in carbonated concrete - Chine-Polito, Bruno (2024)
In the construction sector, the concrete and the steel bars represent still the key components, although they are very vulnerable by the atmospheric agents, as in the case of their degradation caused by corrosion. In this work we present a computational modelling work of reinforced bars corrosion in a carbonated concrete, based on experimental data obtained form an accelerated carbonation process and successive corrosion of metallic bars. The model has been completed incorporating experimental kinetic data of the electrochemical electrode reactions linked to the carbonation front progress. Starting from the experimental values of corrosion potential, corrosion current density, and anodic and cathodic slopes of the Tafel curve, the values of anodic and cathodic exchange currents have been computed and then used to simulate the corrosion of the reinforcing bars in concrete samples.